Writing back : American expatriates and narratives of return - Winnett, Susan (Baltimore : Johns Hopkins University Press, 2013)
"The migration of American artists and intellectuals to Europe in the early twentieth century has been amply documented and studied, but few scholars have examined the aftermath of their return home. Writing Back focuses on the memoirs of modernist writers and intellectuals who struggled with their return to America after years of living abroad. Susan Winnett establishes repatriation as related to but significantly different from travel and exile. She engages in close readings of several writers-in-exile, including Henry James, Harold Stearns, Malcolm Cowley, and Gertrude Stein. Writing Back examines how repatriation unsettles the self-construction of the "returning absentee" by challenging the fictions of national and cultural identity with which the writer has experimented during the time abroad. As both Americans and expatriates, these writers gained a unique perspective on American culture, particularly in terms of gender roles, national identity, artistic self-conception, mobility, and global culture."--Project Muse
Introduction: writing back: American expatriates' narratives of return -- Framing the un-scene/writing the wrongs : Henry James's text of America -- An intellectual is being beaten : the escape and return of Harold E. Stearns -- Wo Mama war, soll Dada werden : Malcolm Cowley's odyssey of legitimation -- Everybody's autobiography : the remaking of an American -- Postcript.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Stein, Gertrude, -- 1874-1946 -- Criticism and interpretation; Cowley, Malcolm, -- 1898-1989 -- Criticism and interpretation; Stearns, Harold, -- 1891-1943 -- Criticism and interpretation; James, Henry, -- 1843-1916 -- Criticism and interpretation; Stein, Gertrude, -- 1874-1946 -- Criticism and interpretation; Cowley, Malcolm, -- 1898-1989 -- Criticism and interpretation; Stearns, Harold, -- 1891-1943 -- Criticism and interpretation; James, Henry, -- 1843-1916 -- Criticism and interpretation; Cowley, Malcolm, -- 1898-1989; James, Henry, -- 1843-1916; Stearns, Harold, -- 1891-1943; Stein, Gertrude, -- 1874-1946; Identity (Psychology) in literature; Expatriate authors -- Psychology; Autobiography; American prose literature -- 20th century -- History and criticism; Europe -- In literature; United States -- In literature; Autobiographies as Topic; Identité (Psychologie) dans la littérature.; Écrivains expatriés -- Psychologie; Autobiographie; Prose américaine -- 20e siècle -- Histoire et critique; autobiography (genre); LITERARY CRITICISM -- American -- General; American prose literature; Autobiography; Identity (Psychology) in literature; Literature; Europe; United States; 1900-1999; Electronic books; Criticism, interpretation, etc